Design and Build Miniature Production System (MPS) on Handling Station and Sort Station Using Cascade Controller - Muhamad Yusuf; Sugeng Dwi Riyanto; Hera Susanti (Faculty of Engineering, Universitas Tanjungpura, 2022)
The sorting process based on color generally still uses human power. This has a weakness, i.e., human judgements that are subjective and inconsistent, and work that is done repeatedly can cause saturation. So, the purpose of this research is to create a sorting system in Miniature Production System (MPS) that can select objects based on color using a TCS3200 color sensor. The novelty of this research is that it can detect primary and secondary colors of an object. The process of moving objects from the storage unit to the sorting section uses a pneumatic cylinder which acts as a handling station. The handling station uses 3 cylinders to move the vertical, horizontal axes and clamp the workpiece. The movement of each cylinder is regulated by a Programmable Logic Controller (PLC) where the ladder diagram is based on the step diagram. Simplification of the step diagram is achieved by using a cascade controller. The testing results shows that this system can sort objects by color with a success rate of 86%. Tests on the handling station show that the average workpiece removal process takes 11.30 seconds with air pressure of 4-5 bar in the cylinder.